2013
DOI: 10.1016/j.cell.2013.05.046
|View full text |Cite
|
Sign up to set email alerts
|

OTU Deubiquitinases Reveal Mechanisms of Linkage Specificity and Enable Ubiquitin Chain Restriction Analysis

Abstract: SummarySixteen ovarian tumor (OTU) family deubiquitinases (DUBs) exist in humans, and most members regulate cell-signaling cascades. Several OTU DUBs were reported to be ubiquitin (Ub) chain linkage specific, but comprehensive analyses are missing, and the underlying mechanisms of linkage specificity are unclear. Using Ub chains of all eight linkage types, we reveal that most human OTU enzymes are linkage specific, preferring one, two, or a defined subset of linkage types, including unstudied atypical Ub chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
719
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 519 publications
(769 citation statements)
references
References 57 publications
31
719
2
1
Order By: Relevance
“…A previous report with several USP proteins, which includes the homologous USP25, showed only minor differences against all eight diubiquitin substrates (39). In contrast, the deubiquitinating activity of USP28 against diubiquitin linkages resembles the OTU DUB family, where members are specific for one or a small subset of diubiquitin linkages types (40). It is interesting that in addition to the most common Lys 48 and Lys 63 linkages, Lys 11 is preferred by USP28 in our diubiquitin cleavage analysis (Fig.…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…A previous report with several USP proteins, which includes the homologous USP25, showed only minor differences against all eight diubiquitin substrates (39). In contrast, the deubiquitinating activity of USP28 against diubiquitin linkages resembles the OTU DUB family, where members are specific for one or a small subset of diubiquitin linkages types (40). It is interesting that in addition to the most common Lys 48 and Lys 63 linkages, Lys 11 is preferred by USP28 in our diubiquitin cleavage analysis (Fig.…”
mentioning
confidence: 51%
“…In contrast to the other DUBs families, such as the OTU DUBs (40), most of the members of the USP family have been reported to display a promiscuous deubiquitinating activity preference in an assay against the eight possible diubiquitin linkages (39). An exception to this is the tumor suppressor CYLD, which possesses specific deubiquitinating activity for Lys 63 -linked ubiquitin chains synthesized in response to cytokine-mediated activation of TRAF2 and TRAF3 ubiquitin E3 ligases, thus antagonizing NF-B signaling (13).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ubiquitin (Ub)-substrate isopeptide bonds can be cleaved by deubiquitinases (DUBs). Five DUB families have been identified including ovarian tumor proteases (OTUs) [15]. OTUB1 is an OTU family DUB cysteine protease highly specific for cleaving Lys48-linked polyubiquitin chains, which targets proteins for proteasomal degradation [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…However, UBXL has low sequence identity of less than 15% to UBX and furthermore lacks the signature motif of UBX. So far, the structure of the OTU domain from yeast complexed with ubiquitin has been produced (18), and recently it has been demonstrated that YOD1, the mammalian homolog of OTU1, has high specificity for Lys 11 -linked ubiquitin chains in a report that shows the complex structure of YOD1 with Lys 11 -linked diubiquitin (19). To understand how OTU1 interacts with VCP on a molecular level and to gain insight into how this interaction regulates the ERAD pathway, we carried out a structural study on N VCP complexed with UBXL OTU1 and performed negative staining electron microscopy (EM) and biochemical studies of the full-length proteins.…”
mentioning
confidence: 99%